Food safety regulatory requirements with potential effect on exports of aquaculture products from developing countries to the EU and US - Bagumire1, Ananias; Todd 2, Ewen CD; Nasinyama 3, George W.; Muyanja4, Charles (Global Journal of Food and Agribusiness Management, 2011)
Aquaculture production presents unique sources of food safety hazards in addition to those common to fish and fishery products and general food stuffs. Hence, its products attract stricter controls in international trade especially in the markets within industrial countries like in the European Union (EU) and the United States (US). Environmental chemical and microbial contamination of fish culture containments, fish infection and disease, use of veterinary drugs, improper use of chemicals, use of genetically modified organisms (GMOs), and improper husbandry and hygiene practices are the major sources of food safety challenges in aquaculture. Most food safety legislations applied in major prime markets of fish like EU and US are aimed at regulating against these challenges, which means that developing countries that do not address these food safety issues may have their access to these markets blocked. Inspection and certification of aquaculture farms and application of Hazard Analysis and Critical Control Points (HACCP) and Good Aquaculture Practices (GAqPs) have been recommended as good approaches for limiting the introduction of potential food hazards in aquaculture products. These approaches are as well incorporated in international regulations and those applying to producers and traders in US and EU to prevent production and trade of unsafe food products. Already most food safety regulatory oversights applied in industrialised countries recognise the concept of equivalence, implying that developing countries that plan to export their products have to comply with the requirements in importing countries. This paper identifies international food safety and other regulatory requirements for production and trade of food from aquaculture and provides an analysis of legislations applied in the European Union (EU) and United States (US) markets that may impact on trade of food of aquaculture origin from developing countries